2014
DOI: 10.1128/jcm.01848-14
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Pneumocystis jirovecii Dihydropteroate Synthase and Dihydrofolate Reductase Genes in HIV-Infected Patients in China

Abstract: We investigated Pneumocystis jirovecii dihydropteroate synthase (DHPS) and dihydrofolate reductase (DHFR) genes for mutations in 25 Chinese HIV-infected patients with P. jirovecii pneumonia. We identified DHPS mutations in 3 (12%) patients and DHFR mutations in 1 (4%) patient. The prevalence of DHPS and DHFR mutations in China remains low, as it does in other developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Furthermore, the rates of DHPS and DHFR mutations were still very low [12,[35][36][37]. In this study, DHPS WT and DHFR 312C were observed at the DHPS and DHFR locus and no other mutations were detected, consistent with the prior studies reported in PR China [12,34,37]. This low prevalence of DHPS and DHFR mutations was not only demonstrated in China but also in other developing countries such as Brazil, South Africa and Thailand [38][39][40].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the rates of DHPS and DHFR mutations were still very low [12,[35][36][37]. In this study, DHPS WT and DHFR 312C were observed at the DHPS and DHFR locus and no other mutations were detected, consistent with the prior studies reported in PR China [12,34,37]. This low prevalence of DHPS and DHFR mutations was not only demonstrated in China but also in other developing countries such as Brazil, South Africa and Thailand [38][39][40].…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have demonstrated that treatment failures of PJP are closely correlated with the high mutation rates of DHPS and DHFR gene and the frequencies of mutations in DHPS gene are greatly higher than that in DHFR, indicating that the DHPS mutations are caused by the pressure of drug selection but not random occurrences [31,32]. The DHPS wild-type (WT) sequence was more frequent displaying in P. jirovecii DHPS genotype, while WT and DHFR 312 synonymous mutations (nucleotides at position 312C) were common in DHFR genotype [7,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasingly convincing evidence from genotyping studies supporting recent acquisition in at least some cases. This includes the presence of different genotypes between the first and second episodes in patients with recurrent infection (366,524,525); outbreaks of PCP caused by a single strain within one or more organ transplant centers, based on highly discriminative msg-RFLP or MLST, as discussed below (355,357,526,527); and the occurrence of sulfa resistance-associated dhps mutations in patients without prior exposure to sulfa drugs (54,57,528,529). Recent acquisition is further supported by the high prevalence of multistrain coinfections as discussed in the preceding section.…”
Section: Strain Variation Of P Jiroveciimentioning
confidence: 99%
“…This result is consistent with those of previous studies of Chinese people. Kazanjian et al revealed a DHPS gene mutation rate of 6.7% (1/15) in AIDS-PCP in Beijing[ 30 ], Deng et al identified DHPS mutations in 12.0% (3/25) patients from Guangzhou[ 31 ], the prevalence of P . jirovecii DHPS mutations in this study is not significantly higher than those of these previous studies ( P = 0.858, P = 0.137, respectively).…”
Section: Discussionmentioning
confidence: 99%